Recent Trends in the Synthesis and Mechanistic Implications of Phenanthridines. Issue 5 (16th February 2021) - Talukdar, Vishal; Vijayan, Ajesh; Kumar Katari, Naresh; Radhakrishnan, K. V.; Das, Parthasarathi
Abstract: Phenanthridine derivatives are one of the most intensively studied families of biologically active compounds. There has been considerable scientific interest in the turn of this century in the synthesis of these N ‐containing heterocycles as they are prevalent in many alkaloids and also possess striking biological activities including antibacterial, antifungal, antitumor activities. In this regard, a number of synthetic approaches toward the construction of phenanthridine moieties with various substituents, and to increase their yield have been developed by the synthetic organic community. Even though many researchers have developed various innovative methods for the synthesis of phenanthridine derivatives for the past few years, still there is substantial scope for the discovery of novel synthetic methods. In this review, the latest developments in the diverse synthetic strategies of phenanthridine derivatives in the presence and absence of metals were described. The present review also enlightens the use of different reagents, the diversity of the substrates identified, and the plausible mechanisms unravelled towards the construction of these biologically relevant scaffolds. Abstract :